HUKUM TANAH: Konstruksi Hukum Penyelesaian Sengketa Gadai Tanah Berbasis Hukum Adat Di Kabupaten Ngawi - Nugroho, Sigit Sapto; Pudjiono, Moch Juli; Tohari, Muhammad (Universitas Merdeka Madiun, 2019)
The specific purpose of this study is to describe why people (people) in Ngawi Regency still do a lot of land pawning and to find the concept of construction of customary law based pawn dispute settlement law. This study uses empirical legal research methods, namely a legal research method that seeks to see the law in a real sense or, examine how the law works in society. Research location in Ngawi Regency.The results of the study show that why people do land pawning because some people need money in an easy and uncomplicated way due to economic needs, capital requirements for businesses, hospital expenses, education costs, marriage costs and other needs . Land pawning is carried out according to customary law based on mutual trust and enthusiasm to help between relatives, neighbors and the community. The concept of legal construction as an effort to resolve land pawn disputes can be carried out in two ways, namely non-ligation, namely through deliberation and consensus through negotiations between the parties or involving mediators namely Village Heads or community leaders who are considered capable of resolving. The second method is the way of litigation through a lawsuit in the District Court, which is the last way to get justice.